Alternative Planning Slope Stabilization on Roadway Case Study : Landslide on Tabone-Polewali Road Section KM 168+790 to 168+820 - Ismi Istiqamah; Mohamad Khoiri; Mahendra Andiek Maulana; Bambang S. Razak (Journal of Infrastructure & Facility Asset Management, 2025)
The Tabone-Polewali road section is a national road in the West Sulawesi Province that connects the Polewali Mandar Regency and Mamasa Regency. The terrain along this section consists of fairly steep slopes. In 2021, landslides occurred at several points along the Tabone-Polewali road, one of which happened at KM 168+790 to 168+820 during heavy rain. The cause of the landslides is estimated to be water flowing from the upper slope to the lower slope without effective water runoff management. No measures have been taken at this location, making it still hazardous for road users. There are several alternative designs for permanent mitigation, including bored. Slope stability existing analysis was conducted using the Limit Equilibrium Method and Finite Element Method (FEM) for slope reinforcement stability analysis. The results obtained from this study show that the Safety Factor for the existing condition is 1,09. The Safety Factor for the alternative design using bored piles is 1,277 where this has met the minimum safety factor value requirements.